2017
DOI: 10.1007/82_2017_71
|View full text |Cite
|
Sign up to set email alerts
|

Cell and Gene Therapy for HIV Cure

Abstract: As the HIV pandemic rapidly spread worldwide in the 1980s and 1990s, a new approach to treat cancer, genetic diseases, and infectious diseases was also emerging. Cell and gene therapy strategies are connected with human pathologies at a fundamental level, by delivering DNA and RNA molecules that could correct and/or ameliorate the underlying genetic factors of any illness. The history of HIV gene therapy is especially intriguing, in that the virus that was targeted was soon co-opted to become part of the targe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(35 citation statements)
references
References 246 publications
0
33
0
Order By: Relevance
“…Nevertheless, this case was not further reproduced; a recent work by Colonna et al in cART-suppressed non-human primates infected by SIV showed how allopoietic hematopoietic cell transplantation is insufficient for HIV eradication despite high-level donor chimerism and graft versus host disease due to the persistence of HIV in multiple sites including the brain [123]. Nowadays, several strategies based on gene and cell therapy have been tested in order to evaluate HIV cure approaches from in vitro studies to clinical trial [124]. These include engineering HIV-specific immunity in T-cells, gene editing approaches to render all blood cells in the body HIV-resistant starting from the proof of concept of the "Berlin patient", and a combination of both these strategies.…”
Section: Gene and Cell Therapymentioning
confidence: 99%
“…Nevertheless, this case was not further reproduced; a recent work by Colonna et al in cART-suppressed non-human primates infected by SIV showed how allopoietic hematopoietic cell transplantation is insufficient for HIV eradication despite high-level donor chimerism and graft versus host disease due to the persistence of HIV in multiple sites including the brain [123]. Nowadays, several strategies based on gene and cell therapy have been tested in order to evaluate HIV cure approaches from in vitro studies to clinical trial [124]. These include engineering HIV-specific immunity in T-cells, gene editing approaches to render all blood cells in the body HIV-resistant starting from the proof of concept of the "Berlin patient", and a combination of both these strategies.…”
Section: Gene and Cell Therapymentioning
confidence: 99%
“…To introduce such modifications in vivo, it will be necessary to design vectors that can carry the appropriate editing systems to selected target cells after percutaneous (e.g., intravenous or intramuscular) administration. Active work in this area [55][56][57] has already highlighted the capabilities of viral (e.g., AAV and lentiviral) vectors as well as ligand-directed lipid nanoparticles, ribonucleoprotein complexes, synthetic nucleocapsids, and exosomes; given commercial opportunities in areas like oncology, it is inevitable that even more options will surface in the future.…”
Section: Making Gene Therapies Accessible To Allmentioning
confidence: 99%
“…Finally, a lot of effort is currently put into gene therapy concepts targeting HIV-infected cells. 24 , 25 Here, T cells have been modified to express antisense transcripts in an attempt to confer protection from HIV infection. 26 Similarly, the modification of T cells with membrane-anchored peptides inhibiting cell-virus fusion as well as TCRs recognizing viral antigens has been explored as a treatment option for HIV patients resistant to antiretroviral therapy.…”
Section: Main Textmentioning
confidence: 99%